Effect Of Sea Moisture Content On Corrosion Hull Of A Warship Made By PT Pal Indonesia - Lamablawa, Florianus; Aritonang, Sovian (International Journal of Science, Technology & Management, 2023)
Seawater temperature ranges from -2 0 c to 300 c. Low temperatures are usually found in seawater around the poles and on the deep seabed. Meanwhile, high seawater temperatures are found in the sea in the Arid area. The Red Sea and Bab El Mandeb have temperatures of about 290 c to 300. Corrosion is a subject matter that concerns various disciplines, or in other words, it connects elements of physics, chemistry, metallurgy, electronics and engineering. This study uses the literature review study method to collect, identify, evaluate the effect of seawater content on the corrosion of the hulls of warships made by PT Pal Indonesia. An effective corrosion control strategy should be selected with the selection of suitable coatings for the marine environment. Hull plating with paint has a special function to protect the construction of the hull, especially those located below the waterline and the construction of the ship above the waterline.